New insights in dermatophyte research. (10th March 2018) - Gräser, Yvonne; Monod, Michel; Bouchara, Jean-Philippe; Dukik, Karolina; Nenoff, Pietro; Kargl, Alexandra; Kupsch, Christiane; Zhan, Ping; Packeu, Ann; Chaturvedi, Vishnu; de Hoog, Sybren
Abstract: Dermatophyte research has renewed interest because of changing human floras with changing socioeconomic conditions, and because of severe chronic infections in patients with congenital immune disorders. Main taxonomic traits at the generic level have changed considerably, and now fine-tuning at the species level with state-of-the-art technology has become urgent. Research on virulence factors focuses on secreted proteases now has support in genome data. It is speculated that most protease families are used for degrading hard keratin during nitrogen recycling in the environment, while others, such as Sub6 may have emerged as a result of ancestral gene duplication, and are likely to have specific roles during infection. Virulence may differ between mating partners of the same species and concepts of zoo- and anthropophily may require revision in some recently redefined species. Many of these questions benefit from international cooperation and exchange of materials. The aim of the ISHAM Working Group Dermatophytes aims to stimulate and coordinate international networking on these fungi.